Combining of ETHOS operating ergonomic platform, three-dimensional laparoscopic camera, and radius surgical system manipulators improves ergonomy in urologic laparoscopy: comparison with conventional laparoscopy and da Vinci in a Pelvi trainer - Tokas, Theodoros; Gözen, Ali Serdar; Tschada, Alexandra; Fiedler, Marcel; Rassweiler, Jens (European urology focus, 2017)
Background: Posture, vision, and instrumentation limitations are the main predicaments of conventional laparoscopy. Objective: To combine the ETHOS surgical chair, the three-dimensional laparoscope, and the Radius Surgical System manipulators, and compare the system with conventional laparoscopy and da Vinci in terms of task completion times and discomfort. Design, setting, and participants: Fifteen trainees performed the three main laparoscopic suturing tasks of the Heilbronn training program (IV: simulation of dorsal venous complex suturing; V: circular suturing of tubular structure; and VI: urethrovesical anastomosis) in a pelvi trainer. The tasks were performed conventionally, utilizing the three devices, and robotically. Task completion times were recorded and the surgeon discomfort was evaluated using questionnaires. Outcome measurements and statistical analysis: Task completion times were compared using nonparametric Wilcoxon signed rank test and ergonomic scores were compared using Pearson chi-square test. Results and limitations: The use of the full laparoscopic set (ETHOS chair, three-dimensional laparoscopic camera, Radius Surgical System needle holders), resulted in a significant improvement of the completion time of the three tested tasks compared with conventional laparoscopy (p<0.001) and similar to da Vinci surgery. After completing Tasks IV, V, and VI conventionally, 12 (80%), 13 (86.7%), and 13 (86.7%) of the 15 trainees, respectively, reported heavy total discomfort. The full laparoscopic system nullified heavy discomfort for Tasks IV and V and minimized it (6.7%) for the most demanding Task VI. Especially for Task VI, all trainees gained benefit, by using the system, in terms of task completion times and discomfort. The limited trainee robotic experience and the questionnaire subjectivity could be a potential limitation. Conclusions: The ergonomic laparoscopic system offers significantly improved task completion times and ergonomy than conventional laparoscopy. Furthermore, it demonstrates comparable results to robotic surgery. Patient summary: The study was conducted in a pelvi trainer and no patients were recruited.